Drawing techniques as tools for the evaluation of scholastic integration and emotional components in primary and secondary school: A cross-sectional study - La Grutta, Sabina; Piombo, Marco Andrea; Riolo, Martina; Spicuzza, Vittoria; Cianciolo, Umberto Maria; Andrei, Federica; Trombini, Elena; Epifanio, Maria Stella (Frontiers in Psychology, 2023)
In the last decades many studies have been emphasizing the role of emotion on psycho-educational processes during childhood, such as scholastic integration. Emotional variables in childhood can be assessed through projective graphic techniques, as they allow children to use kinetic components of the draws to communicate emotions. In the present study, we explored how graphic techniques evaluate children’s emotional state and integration and the extent to which such techniques are sensitive to assess children’s individual differences from primary to secondary school. Data have been collected from 2014 to 2020: 1757 couple of draws were collected, from primary school children (N=1270; F=643 [50,6%]; Age=8.6; SD=1.31) and secondary school children (N=487; F=220 [45.2%]; Age=11.72; SD=0.70) from 8 School in Sicily and over 60 different classrooms. The Drawn Stories Technique and the Classroom Draw were used to assess children current emotional state and scholastic integration. Pearson correlation showed significant relationships between Drawn stories technique and both sex (r = − 0.168 p < .01) and age (r=0.69 p>0.01), while Classroom Drawing total score showed significant relationship with female sex (r=-0.060 p>0.05) but no significant relationship with age (r=-0.14; p >0.05). Linear regression analysis showed sex is a significant predictor of Negative Outcomes of Drawn stories technique explained a total of 2.4% (F 29.090 p < .000) of variance; while no effect of Age was detected (β=-0.28; p >0.05). Regarding the secondary school, the model explained only the 0.4% of variance with Sex as the only significant predictor (p < .001). Findings showed that adequate attention is needed to the emotional-affective world of the learners that influences their relationships and the vision of themselves within the class-group, not neglecting their individual and gender differences but allowing them to take advantage of a communicative-expressive channel functional to their psychic life. Drawing techniques alone seems to be not as such sufficient to explain children individual differences in the classroom but could be useful to teacher to thinking about the emotional climate of their classroom in order to facilitate teacher and children dialogues, modulate didactical materials and detect and prevent some future integration and group class functioning.